Reestructuración comercial y administrativa en la empresa Ferreimportaciones D&D S.A.S., ubicada en la ciudad de Bogotá D.C. (2019)
To identify the current situation of the company, it was initially decided to make use of diagnostic tools such as the PESTAL analysis (Colombia and Bogotá). Similarly, a sectoral analysis was carried out and subsequently carry out a self-diagnosis of the Bogota Chamber of Commerce. To complete a DOFA analysis (Weaknesses, opportunities, strengths and threats), where the position of the company in the sector was identified and strategies were proposed for the context in which the company carries out its activities.